Desarrollo de realidad virtual inmersiva aplicada al entorno virtual de la carrera Computación e integración de respuestas inteligentes mediante la implementación de Inteligencia Artificial - Macas Vélez, José Andrés (2025)
This degree work deals with the updating of the virtual tour system of Carrera de Computación of Universidad Nacional de Loja, transforming it into a fully immersive environment through the use of virtual reality and artificial intelligence. The MSD-VR methodology was used to structure the development of the system, allowing to optimize its implementation and execution in Meta Quest 2 devices. In addition, the generative model “Gemini 1.5 Pro” was incorporated for the creation of informative avatars with intelligent responses in real time, improving user interaction within the virtual environment in order to increase immersion. The results of this study show a significant improvement in the perceived sense of presence of the sample selected for the application of the SUS test, compared to the previous non-immersive virtual tour system. An increased sense of immersion was achieved due to optimized 3D modeling, smooth interaction, integration of good quality textures and realistic scrolling techniques within the environment. However, challenges related to the optimization of computational resources and the adaptability of the MSD-VR methodology to specific educational projects were identified. The conclusions of the study highlight the effectiveness of immersive virtual reality as a teaching and academic orientation tool. It also recommends the implementation of future improvements, such as the optimization of artificial intelligence and the exploration of new interaction technologies. This work represents an advance in the application of immersive virtual environments in the field of virtual tours, laying the groundwork for its adoption in different areas.